2019
DOI: 10.1111/cogs.12802
|View full text |Cite
|
Sign up to set email alerts
|

Problem Solvers Adjust Cognitive Offloading Based on Performance Goals

Abstract: When incorporating the environment into mental processing (cf., cognitive offloading), one creates novel cognitive strategies that have the potential to improve task performance. Improved performance can, for example, mean faster problem solving, more accurate solutions, or even higher grades at university. 1 Although cognitive offloading has frequently been associated with improved performance, it is yet unclear how flexible problem solvers are at matching their offloading habits with their current performanc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 46 publications
(128 reference statements)
4
32
1
Order By: Relevance
“…Note that novel smartphone applications are, just like robots, created by humans and, also just like robots, likely perceived superior to humans in analytical tasks (compare to Hertz & Wiese, 2019). However, they are not embodied, less present in the news, and usually more specialized in 1 Please note that other factors like performance (Risko et al, 2014;Walsh & Anderson, 2009;Weis & Wiese, 2019b), effort (Ballard et al, 1997;Kool et al, 2010), or trust (de Visser et al, 2012(de Visser et al, , 2016 likely also influence cognitive interactions with humans, computers, and robots, but are addressed in the current paper only insofar as they might be mediated by an associated belief system (i.e., a mental model). a specific domain (e.g., entertainment or finance) than their embodied counterparts.…”
Section: Current Study: Do Mental Models Shape How Cognitive Environmmentioning
confidence: 99%
“…Note that novel smartphone applications are, just like robots, created by humans and, also just like robots, likely perceived superior to humans in analytical tasks (compare to Hertz & Wiese, 2019). However, they are not embodied, less present in the news, and usually more specialized in 1 Please note that other factors like performance (Risko et al, 2014;Walsh & Anderson, 2009;Weis & Wiese, 2019b), effort (Ballard et al, 1997;Kool et al, 2010), or trust (de Visser et al, 2012(de Visser et al, , 2016 likely also influence cognitive interactions with humans, computers, and robots, but are addressed in the current paper only insofar as they might be mediated by an associated belief system (i.e., a mental model). a specific domain (e.g., entertainment or finance) than their embodied counterparts.…”
Section: Current Study: Do Mental Models Shape How Cognitive Environmmentioning
confidence: 99%
“…Although time-minimisation could conceivably benefit individuals by, e.g., freeing up time for them to complete other goals or tasks, it is unlikely that time would be the only consideration when selecting a given strategy for a task; indeed, individuals can and do prioritise other factors over time in some cases ( Dunn et al, 2019 ; Kool et al, 2010 ; Weis & Wiese, 2018 ). For example, Weis and Wiese (2019) demonstrated that an individual’s higher level goals will play a critical role when participants are choosing between alternative strategies. Specifically, the authors found that individuals’ use of a novel external tool that reduced internal processing in a cognitive task varied as a function of whether individuals were provided speed- or accuracy-based instructions.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to the less focused interactions with robot companions like Furby, CO is centered on task-relevant outcomes like providing the solution to an arithmetic or navigation problem. It is known that people can adaptively adjust how frequently they engage in CO depending on the situation (e.g., depending on the time costs of engaging in CO; W. D. Gray et al, 2006;Storm et al, 2017; or on whether speed or accuracy is prioritized; Weis & Wiese, 2019) but sometimes fail to do so because of inaccurate metacognitive judgements like wrongly estimating own EMOTIONAL CONSEQUENCES OF HRI cognitive ability such as underestimating own memory (Gilbert, 2015;Touron, 2015). Current research thus provides a successively clearer picture about what makes people engage in CO.…”
Section: Cognitive Offloading and Its Consequencesmentioning
confidence: 99%